Evaluating Employee Onboarding Program in A Travel Technology Company - Auliaur Rahmah, Arrizqiya; Ginting, Henndy (Green Publisher Indonesia, 2025)
This study examines the effectiveness of PT's onboarding program. Fly Together amid rapid expansion in the APAC region. As a travel technology company, effective onboarding is essential to enable new hires to adapt quickly and achieve organizational goals. This study aims to evaluate the effectiveness of the onboarding program at PT. Flying Together in the Context of the Company's Rapid Expansion in the APAC Region The current practice, which involves many stakeholders such as line managers and HR, faces challenges including inconsistent execution, resource delays, and inadequate follow-up, raising concerns about program effectiveness. This study uses the Socialization Resources Theory (SRT) theory to analyze 17 dimensions of the onboarding program and their relationship with onboarding outcomes, including role clarity, self-efficacy, social integration, and cultural knowledge. The analysis showed that the average score of the onboarding results was 2.65, which indicates the program's ineffectiveness. Correlation analysis shows a strong relationship between onboarding dimensions, such as job resources and supervisor support, and key onboarding outcomes. The mixed research method combined quantitative data from 23 new hires and qualitative interviews with experts. Based on these findings, the study proposes actionable recommendations, including enhanced anticipatory socialization, a formalized friend system, and structured follow-up mechanisms. These upgrades address key gaps, allow new hires to integrate effectively, improve performance, and contribute to the company's success. The study underscores the critical role of well-structured onboarding in achieving employee satisfaction and organizational goals.